2012
DOI: 10.1080/13678868.2012.687625
|View full text |Cite
|
Sign up to set email alerts
|

Minding the gap: exploring differences in perceptions of ethical business cultures among executives, mid-level managers and non-managers

Abstract: This study explored whether perceptions of organizational business ethics differ by hierarchical levels. The study sample included more than 40,000 executives, mid-level managers and non-managerial employees from business organizations in six countries: Brazil, China, Germany, India, the UK and the US. We found that executives provided the most positive assessment of ethical business culture within their respective organizations. Employees' assessments were less positive, and mid-level managers' assessments fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 48 publications
(44 reference statements)
1
25
1
Order By: Relevance
“…In each of these instances, perceptions of executive managers were more aspirational than the perceptions of staff. These findings are consistent with research showing that the perceptions of middle-managers and non-managerial staff tend to be less positive than the perceptions of executive managers concerning strategic elements of the organisation (Ardichvili et al, 2012). Additionally, the findings are in line with the results of a recent organisational review conducted by the OEH, which indicated that there was a need for a greater strategic direction within the parks agency in promoting, managing, and providing nature, culture and heritage tourism experiences (Office of Environment and Heritage NSW, 2014).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In each of these instances, perceptions of executive managers were more aspirational than the perceptions of staff. These findings are consistent with research showing that the perceptions of middle-managers and non-managerial staff tend to be less positive than the perceptions of executive managers concerning strategic elements of the organisation (Ardichvili et al, 2012). Additionally, the findings are in line with the results of a recent organisational review conducted by the OEH, which indicated that there was a need for a greater strategic direction within the parks agency in promoting, managing, and providing nature, culture and heritage tourism experiences (Office of Environment and Heritage NSW, 2014).…”
Section: Discussionsupporting
confidence: 90%
“…This is in contrast to the many differences in perceptions found between OEH executive managers and other OEH staff. The findings are also in contrast to previous research, which found that non-managerial staff members often have less positive perceptions than managers regarding strategic aspects of the organisation (Ardichvili et al, 2012). As such, the findings add to the literature by identifying the factors that potentially explain any differences in perceptions of staff in regard to park benefits.…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…However, findings corroborate Bobek, Hageman and Radtke's (2015) idea that individuals in leadership roles respond differently to ethical challenges when compared to those in non-leadership roles. In fact, Ardichvili, Jondle and Kowske (2012) observed that organisational members in nonleadership positions are accommodating to ethically suspect behaviour. In the context of the developing world, the results may possibly be explained by the generally poor remuneration in the workplace, which increases the attractiveness of deviant behaviour as a way of getting additional income.…”
Section: Discussionmentioning
confidence: 99%